[Elmer on stilts - McKee, David ([S.l.] : Heryin Pub. Corp., 2004)
Elmer the Patchwork Elephant comes up with a plan to save his friends from elephant hunters. Presented in English and Chinese, with an audio CD.
4.3
Preschool
Text in English and traditional Chinese.
Compact disc.
Translated from the English.
Title taken from the colophon; title on t.p. is in traditional Chinese characters.
Keywords: Elmer (Fictitious character : McKee) -- Juvenile fiction; Elephants -- Juvenile fiction; Elmer (Fictitious character : McKee) -- Fiction; Elephants -- Fiction; Chinese language materials -- Bilingual; Elmer (Fictional character : McKee) -- Fiction; Elephants -- Fiction; Bilingual books -- English-Chinese.; Picture books for children